1997
DOI: 10.1177/026921639701100104
|View full text |Cite
|
Sign up to set email alerts
|

Hospice and palliative care in the UK 1994-5, including a summary of trends 1990-5

Abstract: 3 Addington-Hall JM, Karlsen S. Age is not the crucial factor in determining how the palliative care needs of people who die from cancer diVer from those of people who die from other causes. J Palliat Care 1999;15:13-9. 4 Lupu D. Hospice inpatient care: an overview of NHO's 1995 inpatient survey results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 3 publications
3
42
0
5
Order By: Relevance
“…24,25,41 In addition, around 50% of patients admitted to inpatient hospices do not die on the first admission, but return home and come under a home care service. In the U.K., periods of receiving day care are considerably longer, the median length of care is 182 days, and although around 10% of patients are in day for less than one month, almost 30% are in care for one year or more.…”
Section: Transitions Between Curative Palliative and End-of-life Care?mentioning
confidence: 99%
“…24,25,41 In addition, around 50% of patients admitted to inpatient hospices do not die on the first admission, but return home and come under a home care service. In the U.K., periods of receiving day care are considerably longer, the median length of care is 182 days, and although around 10% of patients are in day for less than one month, almost 30% are in care for one year or more.…”
Section: Transitions Between Curative Palliative and End-of-life Care?mentioning
confidence: 99%
“…A gap in the provision of care could then arise, with the families unsure as to where to find suitable help. Neither of the two surveys by Eve et al [3,19] gives any indication as to how many young adults are cared for by adult hospices. It is clear that for many conditions, adult hospices would not be able to provide the care needed even if a referral was made.…”
Section: Discussionmentioning
confidence: 98%
“…On average, children's hospices are smaller than adult hospices. A survey conducted by Eve et al [19] showed most adult hospice to have ten beds although the range was between 2-62 beds.…”
Section: Discussionmentioning
confidence: 99%
“…1 Yet, patients suffering from noncancer advanced illness are generally referred for palliative medical management late in their disease trajectory or not at all. [2][3][4][5] A leading cause of this phenomenon is the difficulty associated with prognostication. When relying solely on clinical experience and intuition, physicians demonstrate poor prognostic accuracy with a tendency to overestimate survival by a factor of 5.3.…”
Section: Introductionmentioning
confidence: 99%